Guarantees according to a social right in the framework of a blurred public-private relationship: it makes difference - Montalbá Ocaña, Carmen (Cuadernos de Trabajo Social, 2014)
The implementation of the Law on Promotion of personal autonomy and care for dependent persons (LAPAD) in Valencia has been a privileged stage for the observation and analysis of the impact of the relationship between public and private in a social right recognized. This article condenses some of the conclusions derived from the case study about the LAPAD life cycle in Valencia during the period 2006-2012. The objective of this research is to identify the reasons that contribute to increase the gap between the legal formulation and effective implementation. The results have focused on those dimensions that refer to the institutional model of the social law and the conditions that enable or impede the full exercise of the law. The public-private relationship in the Valencia social policy context has been identified as one of the obstacles in the recognition and accomplishment of the law.
Keywords: public service; privatization; social laws; dependency; culture of legality